Investigating the Effects of Foreign Aid on the Unemployment Level in Afghanistan: Application of the Auto Regressive Distributed Lag Model - Sakhibaksh Assadi; Muhammad Asef Shaiq; Qiamuddin Andaish (International Journal of Scientific Multidisciplinary Research, 2024)
The correlation between foreign aid and unemployment rates is a topic extensively debated and examined by development economists and policymakers in developing nations. Therefore, this research was conducted to investigate the relationship between foreign aid and the unemployment rate in Afghanistan from 1990 to 2021 and used Auto Regressive Distributed Lag Model. Results showed that the foreign aid variable (ODA) has a statistically significant negative impact on the unemployment level, as evidenced by a coefficient of -0.014. Consequently, the rise in foreign aid results in declining unemployment rates in Afghanistan. Hence, it can be asserted that the expansion of foreign aid is a viable means to foster employment growth in countries. According to this idea, foreign aid is a possible strategic element for decreasing unemployment